High-sensitivity attenuated total internal reflection continuous-wave terahertz imaging. (23rd August 2017) - Liu, Hongxiang; Wang, Yuye; Xu, Degang; Wu, Limin; Yan, Chao; Yan, Dexian; Tang, Longhuang; He, Yixin; Feng, Hua; Yao, Jianquan
Abstract: We demonstrate an attenuated total internal reflection imaging system. The surface information of the sample on top of a prism can be acquired by two-dimensionally scanning this prism moving in the vertical plane with horizontally incident continuous terahertz waves at a fixed height. The principles and feasibility of this method are investigated. The effective imaging area on the prism, image resolution and polarization dependence of contrast enhancement and stability improvement are analyzed. Examples including solid agar, distilled water and porcine tissue are presented, demonstrating the method's advantages of high sensitivity and simple sample preparation. The experimental and theoretical results consistently show that p-polarization contributes to enhanced image contrast and more stable intensity of the attenuated total internal reflected signal.